Consumer-Driven Quality Improvement of Tofu Sumedang: An Integrated Kano–QFD Approach for Strategic Product Development - Pujianto, Totok; Mardawati, Efri; Agustien, Shilvya Dewi (Department of Agro-industrial Technology, University of Brawijaya, 2024)
AbstractSumedang tofu is an Indonesian traditional food with unique characteristics and high cultural value. The product quality in the market still varies, especially regarding tofu's sensory and safety attributes. This study aimed to identify and analyze the quality attributes of Sumedang tofu based on consumer perceptions to formulate relevant technical improvement priorities. The approach integrated the Kano model and Quality Function Deployment method in a systematic analytical framework. The study involved 30 respondents at the Sumedang Tofu Restaurant